International Price Relationship and Volatility Transmission Between Stock Index and Stock Index Futures - ArIsmail bin Ahmad; Fahmi bin Abdul Rahim (Economic Journal of Emerging Markets, 2011)
This study investigates the international price relationship and volatility transmissions between stock index and stock index futures of Malaysia, Hong Kong and Japan. Vector Autoregression (VAR) GJR-GARCH model was applied to the nine years daily price. Japanese markets are the main information producer to the market price changes. International market interdependence only affected the domestic volatility transmission of spot and futures market in Hong Kong. Asymmetric effects exist in all markets and the volatility persistence in each market is high. Finally, the overall conditional correlation estimates for spot and futures markets are higher in the unrestricted model form compared to the restricted model form. Keywords: spot-futures, lead-lags, volatility, VAR GJR-GARCH, Asian financial markets